ANALISIS KONSEKUENSI DISPERSI GAS, KEBAKARAN, DAN LEDAKAN PADA PANGKALAN LPG DI KECAMATAN KRAMAT JATI MENGGUNAKAN PERANGKAT LUNAK ALOHA - Riza Andini Anggraini, (2023)
There were 56 fires in East Jakarta caused by gas. The LPG sub-agent has a chance of fire because it stores a lot of LPG. This study aims to analyze the consequences of leaking LPG cylinders which have the chance of causing gas dispersion, fire, and explosion utilizing the ALOHA software at an LPG base in Kramat Jati District. This quantitative descriptive study used a purposive sampling technique with observation, interviews, ALOHA software, and literature studies. Several 3 Kg LPG cylinders as research objects. Butane and propane were determined for modeling the LPG cylinder leak simulation. Yellow threat zone obtained from modeling gas dispersion, BLEVE/fireball, jet fire, and VCE in butane simulations is 29 meters, 229 meters, 18 meters, and 18 meters and in propane simulations, 57 meters, 231 meters, 26 meters, and 26 meters. From several scenarios, the farthest distance is 231 meters with at-risk populations in the Jagorawi Toll Road, ambulance services, madrasa, kindergarten, field, and several houses in the same area and opposite each other. The use of additional software other than ALOHA needs to be considered to increase the completeness and accuracy of the data